Efficient identification of compounds suppressing protein precipitation via solvent screening using serial deletion mutants of the target protein. (2nd January 2018) - Yunoki, Kaori; Yoshinaga, Sosuke; Takeda, Mitsuhiro; Nagano, Ryohei; Tsuchiya, Yusuke; Sonoda, Akihiro; Tsuji, Tatsuichiro; Hirakane, Makoto; Toda, Etsuko; Terashima, Yuya; Matsushima, Kouji; Terasawa, Hiroaki
Abstract : The control of protein solubility is a subject of broad interest. Although several solvent screening methods are available to search for compounds that enhance protein solubilization, their performance is influenced by the intrinsic solubility of the tested protein. We now present a method for screening solubilizing compounds, using an array of N‐ or C‐terminal deletion mutants of the protein. A key behind this approach is that such terminal deletions of the protein affect its aggregation propensity. The solubilization activities of trial solvents are individually assessed, based on the number of solubilized mutants. The solubilizing compounds are then identified from the screened solvents. In this study, the C‐terminal chemokine receptor‐binding region of the cytoplasmic protein, FROUNT (FNT‐C), which mediates intracellular signals leading to leukocyte migration, was subjected to the multicomponent screening. In total, 192 solution conditions were tested, using eight terminal deletion mutants of FNT‐C. We identified five solvent conditions that solubilized four or five mutants of FNT‐C, and the compounds in the screened solvents were then, respectively, assessed in terms of their solubilization ability. The best compound for solubilizing FNT‐C was 1, 6‐hexanediol. Indeed, 1, 6‐hexanediol bound to FNT‐C and suppressed its precipitation, as showed by NMR and dynamic light scattering analyses. Abstract : Although several solvent screening methods are available to search for compounds that enhance protein solubilization, their performance is influenced by the intrinsic solubility of the tested protein. We present a method for screening solubilizing compounds, using an array of N‐ or C‐terminal deletion mutants of the protein. Such terminal deletions of the protein affect its aggregation propensity.